Design, analysis and validation of a microstrip patch antenna with enhanced coupling for leaf moisture sensing: an IoT approach - Khan, Muhammad Talha; Lin, Xian Qi; Zhe, Chen; Saboor, Abdus (Frontiers in Physics, 2024)
An innovative IoT-based system utilizing a modified slotted microstrip patch antenna with enhanced coupling is presented for precise measurement of leaf moisture content. The antenna employs a rectangular slot above the feed point with an advanced coupling technique to enhance sensitivity. The antenna, fabricated on a 0.8 mm F4B substrate, is designed to resonate within the 2.40 to 3.0 GHz range under unloaded conditions. A parametric analysis focusing on leaf permittivity ranging from 20 to 30 is conducted to determine the antennas’ sensitivity. Experimental measurements of the reflection coefficient (S11) with respect to resonant frequency shift are performed with leaf samples as the samples under test (SUT). Experimental results reveal that the proposed patch antenna’s sensitivity is significantly enhanced, ranging from 0.57 to 1.67 times greater than that of traditional patch antennas for the five leaf samples tested. The antenna exhibits a sensitivity of 0.06 GHz and 0.02 GHz for the modified and enhanced coupling designs, respectively. The mean relative error between predicted and measured moisture content values is low at 0.038. The findings highlight the antenna’s increased sensitivity in detecting leaf moisture content and illustrate the potential of the proposed IoT-based system for real-time agricultural monitoring, marking an advancement in precision farming practices. The study validates the microstrip patch antenna’s capability as a moisture sensor through detailed sensitivity analysis, frequency shift measurements, and regression modeling.